Rigid polyurethane (PUR) and polyisocyanurate (PIR) foam for building applications. Specification for two types of laminated board (roofboards) with auto-adhesively bonded reinforcing facings for use as roofboard thermal insulation for built-up roofs Part 3, (30th September 1987) - British Standards Institution,
No abstract available